Eigenvalue inequalities to submanifolds in pseudo Euclidean space - Bektas, M; Ergüt, M (Indian Nat Sci Acad, 2002)
This paper emphasises the important extensions of eigenvalue inequalities to submanifolds in pseudo Euclidean space. It considers x : M-n -->(phi) S-m(m) -->(i) E-s(m+1) , where phi is an isometric immersion, i is the inclusion, k-type submanifold in pseudo-Euclidean space is given and some eigenvalue inequalities are extended to k-type submanifold of pseudo-Euclidean space.
Keywords: k-type submanifold; Laplacian operator